Oncological outcome of malignant colonic obstruction in the Dutch Stent‐In 2 trial. Issue 13 (9th October 2014) - Sloothaak, D. A. M.; van den Berg, M. W.; Dijkgraaf, M. G. W.; Fockens, P.; Tanis, P. J.; van Hooft, J. E.; Bemelman, W. A.; the collaborative Dutch Stent‐In study group; van Hooft, J. E.; Fockens, P.; Bemelman, W. A.; Dijkgraaf, M. G.; et al.
<x xml:space="preserve">Abstract</x> Background The Stent‐In 2 trial randomized patients with malignant colonic obstruction to emergency surgery or stent placement as a bridge to elective surgery. The aim of this study was to compare the oncological outcomes. Methods Disease recurrence, and disease‐free, disease‐specific and overall survival were evaluated, including a subgroup analysis of patients with a stent‐ or guidewire‐related perforation. Results Of 98 patients included in the original Stent‐In 2 trial, patients with benign (16) or incurable (23) disease were excluded from this study, along with a patient who had withdrawn from the trial. Of the remaining 58 patients, 32 were randomized to emergency surgery (31 resection, 1 stoma only) and 26 to stenting. Unsuccessful stenting required emergency surgery in six patients owing to wire or stent perforation. Locoregional or distant disease recurrence developed in nine of 32 patients in the emergency surgery group and 13 of 26 in the stent group. Disease‐free survival was worse in the subgroup with stent‐ or guidewire‐related perforation. Five of six patients in this subgroup developed a recurrence, compared with nine of 32 in the emergency surgery group and eight of 20 who had unperforated stenting. Conclusion Stent placement for malignant colonic obstruction was associated with a risk of recurrence in this trial, but the numbers are small. There is not enough evidence to refute the approach strongly. Registration number: ISRCTN46462267 ( http://www.controlled‐trials.com).